Measurements of plasma potential and electron temperature by ball-pen probes in RFX-mod - Brotankova, J.; Adamek, J.; Martines, E.; Stockel, J.; Spolaore, M.; Cavazzana, R.; Serianni, G.; Vianello, N.; Zuin, M. (Вопросы атомной науки и техники, 2009)
The ball-pen probe (BPP) is an innovative electric probe for direct measurements of the plasma potential. This probe
was developed in IPP Prague and it is based on the Katsumata probe concept. Combined measurements of the plasma
potential by a BPP and floating potential by a Langmuir probe provide also the value of the electron temperature. First
test of the BPP on the RFX-mod reversed field pinch in Padova has been performed in November 2006. The BPP head,
made of boron nitride, is equipped with four graphite collectors, which are positioned at four different radial positions h
inside four shafts hollow into the probe head. The radial profile of the plasma potential and also the electron
temperature were measured. Кулеподібний зонд – новий тип зонду для прямих вимірюаннь потенціалу плазми. Цей зонд розроблено у
ІТП, в Празі, та засновано на концепції зонду Катсумати. Комбіновані вимірювання плазмового потенцілу
кулеподібним зондом та плаваючого потенціалу Ленгмюрівським зондом дають також величину електронної
температури. Перші випробування зонду в пінчі з оберненим полем на RFX-mod у Падові було проведено у
листопаді 2006 р. Головка зонда, вироблена з нітриду бора, була оснащена чотирма графітовими колекторами,
які були розташовані в чотирьох радіальних положеннях h усередині чотирьох порожнистих циліндричних
отворів в голівці зонда. Виміряно радіальний профіль потенціалу плазми й електронну температуру. Шароподобный зонд – новый тип зонда для прямых измерений потенциала плазмы. Данный зонд разработан
в ИФП, в Праге, и основан на концепции зонда Катсуматы. Комбинированные измерения плазменного
потенциала шароподобным зондом и плавающего потенциала Ленгмюровским зондом дают также величину
электронной температуры. Первые испытания зонда в пинче с обращенным полем на RFX-mod в Падове
проведены в ноябре 2006 г. Головка зонда, сделанная из нитрида бора, оснащалась четырьмя графитовыми
коллекторами, которые размещались в четырех различных радиальных положениях h внутри четырех
пустотелых цилиндрических отверстий в головке зонда. Измерены радиальный профиль потенциала плазмы и
электронная температура.